ESG Impact on LQ45 Stock Returns: Early Appraisal - Rosa, Audrey; Putri, Cherryll; Pangaribuan, Christian (Universitas Trisakti, 2024)
This research investigates the correlation between Environmental, Social, and Governance (ESG) risk scores and stock returns in Indonesia’s LQ45 market from 2016 to 2022, considering the influence of firm size. Analyzing data from 39 LQ45-listed firms, panel data estimations, and the Hausman test, the study reaffirms the well-documented firm size effect, showing smaller firms with higher stock returns. However, it does not identify a significant impact of ESG risk scores on stock returns during the study period. This suggests that ESG practices may not yet significantly influence stock performance in the Indonesian market, possibly due to the nascent stage of ESG adoption, introduced publicly by the Ministry of Finance in 2022. The findings highlight the importance of ongoing research and awareness as Indonesia's corporate governance and investment landscape evolve with respect to ESG considerations.